2019
DOI: 10.1007/s13300-019-00744-6
|View full text |Cite
|
Sign up to set email alerts
|

A Multinational Real-World Study on the Clinical Characteristics of Patients with Type 2 Diabetes Initiating Dapagliflozin in Southern Europe

Abstract: Introduction: A real-world study was performed to describe the clinical characteristics of patients who received dapagliflozin to better understand differences when initiating dapagliflozin in various countries and different prescribing settings. Methods: We assessed pooled data from observational studies carried out in Italy (n = 2484), Spain (n = 564) and Greece (n = 87). The primary objective was to compare the clinical profile of patients initiating dapagliflozin in the three countries. We also evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…A recent study examined the different baseline characteristics of patients who were initiated on dapagliflozin and suggested that this may influence patient outcomes. Whilst we saw differences relating to weight and BMI in different therapy groups, the effect on HbA1c appeared to be consistent [8].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…A recent study examined the different baseline characteristics of patients who were initiated on dapagliflozin and suggested that this may influence patient outcomes. Whilst we saw differences relating to weight and BMI in different therapy groups, the effect on HbA1c appeared to be consistent [8].…”
Section: Discussionmentioning
confidence: 76%
“…At baseline, the mean age was 61 ±10 years, HbA1c 82.6 ±15.7 mmol/mol, weight 106 ±21 kg, BMI 37 ±7 kg/m 2 . The sample comprised of 101 patients (43 males, 58 females) with a median duration of diabetes of 12 years (interquartile range [8][9][10][11][12] and a median duration of dapagliflozin treatment of 44 months (range 36-82).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to examine whether these results can be replicated in Southern Europe areas other than Italy, the only countries of this region included and only regarding the assessment of renal outcomes in the CVD REAL available studies [ 19 ]. It is also important to consider that Fadini et al reported that there are country-specific differences in the profile and characteristics of patients initiating dapagliflozin in Southern Europe [ 31 ]. In their real-world practice study, including patients from Italy, Spain, and Greece, the authors found that the SGLT2i dapagliflozin was initiated at different stages depending on the country, with significant differences regarding age, mean T2DM duration, and the presence of comorbidities (e.g., retinopathy, prior stroke, MI, or CVD) [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to consider that Fadini et al reported that there are country-specific differences in the profile and characteristics of patients initiating dapagliflozin in Southern Europe [ 31 ]. In their real-world practice study, including patients from Italy, Spain, and Greece, the authors found that the SGLT2i dapagliflozin was initiated at different stages depending on the country, with significant differences regarding age, mean T2DM duration, and the presence of comorbidities (e.g., retinopathy, prior stroke, MI, or CVD) [ 31 ]. The authors concluded that the observed geographic heterogeneity might not only have an impact in the glucose-lowering effectiveness of SGLT2i but also in the protective CV and renal outcomes.…”
Section: Introductionmentioning
confidence: 99%